No longer a slumdog : bringing hore to children in crisis - Yohannan, K. P., 1950- (Gospel for Asia, 2011)
Read about an abandoned girl who found hope at the end of the railroad tracks, a young boy who escaped after years of forced servitude, and many others whose lives have been redeemed. You'll be captivated by this powerful move of God as K.P. Yohannan leads you on a journey through the slums and villages of South Asia into the hearts and lives of these precious children.